Polyaspartic Acid‐Calcium‐Lanthanum Complexes Induce Antibacterial Remineralization of Dentin and In‐Depth Occlusion of Dentinal Tubules - Ling Zhu; Wei Liu; Yizhou Zhang; Zhifang Wu; Yiru Wang; Yuedan Xu; Haiyan Zheng; Hongli Zhang; Mengfei Yu; Xiaoting Jin; Zhe Wang; Zihuai Zhou; et al. (Advanced Science, 2025)
Abstract Dental caries is a global oral dilemma leading to demineralization of tooth hard tissues and exposure of dentinal tubules (DTs). Multifunctional restorative strategies, including remineralization, antibacterial properties, and DT occlusion, are urgently needed for dental caries management but remain a significant challenge. Herein, the polyaspartic acid‐calcium‐lanthanum suspension (5 g L−1‐3.06 м‐0.34 м) followed by phosphate solution (2.04 м) is adopted to conduct polyelectrolyte‐cation complexes pre‐precursor process. This strategy, for the first time, successfully induces La‐doped intrafibrillar mineralization of collagen fibrils with lanthanum‐doped hydroxyapatite (La‐HAp). After sequential application of two mineralization media, the demineralized dentin is fully remineralized and the DTs are deeply occluded to a depth of 100 µm with La‐HAp after 7 d of incubation in artificial saliva or oral cavity of rabbit. The remineralized dentin demonstrates antibacterial properties against cariogenic bacteria (Streptococcus mutans) both in vitro and in vivo, and its mechanical properties are almost restored to those of intact dentin. The mineralization media cause no apparent irritation to oral mucosa or dental pulp. Hence, this multifunctional strategy confers the remineralized dentin surface with antibacterial properties and blocks the invasion of cariogenic bacteria through DTs, providing insight into the clinical management of dentin caries accompanied by dentin hypersensitivity.